An integrated method to evaluate and monitor the conservation state of coralligenous habitats: The INDEX-COR approach. Issue 1 (15th July 2017) - Sartoretto, Stéphane; Schohn, Thomas; Bianchi, Carlo Nike; Morri, Carla; Garrabou, Joaquim; Ballesteros, Enric; Ruitton, Sandrine; Verlaque, Marc; Daniel, Boris; Charbonnel, Eric; Blouet, Sylvain; David, Romain; et al.
Abstract: A new method based on photographic sampling coupled with in situ observations was applied to 53 stations along the French Mediterranean coast, to assess the integrity of coralligenous reefs affected by different levels of anthropogenic pressure. The conservation state of the assemblages characterizing these habitats was then assessed by an index – the INDEX-COR – that integrates three metrics: (i) the sensitivity of the taxa to organic matter and sediment deposition, (ii) the observable taxonomic richness, and (iii) the structural complexity of the assemblages. The sensitivity of INDEX-COR was tested and showed good correlation with the Level of Pressure calculated for each station according to expert judgment and field observations. Highlights: A large dataset is obtained about an emblematic and rich marine habitat of Mediterranean Sea. A large geographic and bathymetric area are covered by the study. A non-destructive method is proposed with a special consideration given to the needs of MPA's stakeholders. A global ecological index is proposed to describe the conservation state of the coralligenous habitat.